1972
DOI: 10.1136/jcp.25.6.512
|View full text |Cite
|
Sign up to set email alerts
|

The relation of total body potassium to height, weight, and age in normal adults

Abstract: SYNOPSIS Total body potassium was measured in 103 healthy adults using a shadow-shield wholebody monitor of high sensitivity. The standard deviation from regression was smaller when total body potassium was correlated with height than with weight and was further reduced, to about 9 %, in a multiple regression using height and age. The advantages of this relationship over indices involving weight are discussed. The smallest standard deviation from regression, 7-5 %, was obtained when total body potassium was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1
4

Year Published

1978
1978
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(92 citation statements)
references
References 15 publications
(12 reference statements)
6
81
1
4
Order By: Relevance
“…Thomsen et al (1986) have shown that BMC/lean body mass (LBM) is an effective correction for both height and weight. LBM was caculated according to the equation of Boddy et al (1972) and has previously been shown to fit closely with LBM measured by dual photon absorptiometry . We used both BMC and BMC/ LBM measurements in the men studied.…”
Section: S and Methodsmentioning
confidence: 98%
“…Thomsen et al (1986) have shown that BMC/lean body mass (LBM) is an effective correction for both height and weight. LBM was caculated according to the equation of Boddy et al (1972) and has previously been shown to fit closely with LBM measured by dual photon absorptiometry . We used both BMC and BMC/ LBM measurements in the men studied.…”
Section: S and Methodsmentioning
confidence: 98%
“…The gold standard for measuring body composition in a two-compartment model has been underwater weighing (UWW), which measures body density from which fat and lean mass content are estimated by assuming standard ®gures for density of these components (Siri, 1961). Other robust methods include the total-body potassium method, measuring intracellular¯uid by detecting the natural radioactive 40 K isotope (Boddy et al, 1972), and measurement of total body water by dilution of a deuterium-labeled water dose (Schoeller et al, 1980). More complicated multicompartment models of body composition that include bone mass are under development (Harsha & Bray, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In no subject was the measured TBK significantly less than both predicted normal values (Boddy et al, 1972). However, in two subjects (6 and 9) the measured value was less than that estimated from height and age only.…”
Section: Discussionmentioning
confidence: 64%
“…The procedure has been described in detail previously (Boddy et al, 1971). The measured TBK in each subject was compared with the expected normal values and range estimated from height and age and from height, weight, and age (Boddy et al, 1972). Exchangeable body potassium was measured by the general method of Davies and Robertson (1973) except that 43K alone was administered.…”
Section: Methodsmentioning
confidence: 99%